Question
upstudy study bank question image url

(b) Simplify the following: \( \begin{array}{lll}\text { (1) } 2^{x} \cdot 2^{x} & \text { (2) }\left(2^{5}\right)^{x} & \text { (3) }\left(3^{x}\right)^{3} \\ \text { (4) } 2^{x} \cdot 2^{3} & \text { (5) }\left(5^{3} \cdot 3^{5}\right)^{x} & \text { (6) } 9^{x} \cdot 3^{2 x} \\ \text { (7) } 81^{x} \cdot 27^{2 x} & \text { (8) } \frac{5^{x} \cdot 5^{x}}{25^{x}} & \text { (9) } \frac{\left(2^{x}\right)^{3} \cdot 2^{x}}{16^{x}} \\ \text { (10) } \frac{7^{x} \cdot 7^{2 x}}{\left(7^{2} \cdot 7\right)^{x}} & \text { (11) } \frac{25 \cdot 9^{x}}{3^{x} \cdot 3^{x} \cdot 5} & \text { (12) } \frac{\left(2^{x}\right)^{3} \cdot 27^{x}}{8^{x} \cdot\left(3^{2}\right)^{x} \cdot 3^{x}} \\ \text { (13) } \frac{12^{x} \cdot 3^{-x}}{2 \cdot 4^{x}} & \text { (14) } \frac{32^{x}}{4^{x}} & \end{array} \)

Ask by Chadwick Donnelly. in South Africa
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the simplified answers for each expression: 1. \( 2^{2x} \) 2. \( 2^{5x} \) 3. \( 3^{3x} \) 4. \( 2^{x+3} \) 5. \( 5^{3x} \cdot 3^{5x} \) 6. \( 3^{4x} \) 7. \( 3^{10x} \) 8. \( 1 \) 9. \( 1 \) 10. \( 1 \) 11. \( 5 \) 12. \( 1 \) 13. \( \frac{1}{2} \) 14. \( 2^{3x} \)

Solution

We wish to “simplify” each expression so that the answer is written in a single exponential form (or in simplest form). One acceptable set of answers is given below. Let’s go through each one. ───────────────────────────── (1) Simplify 2ˣ · 2ˣ When multiplying powers with the same base add the exponents:   2ˣ · 2ˣ = 2^(x + x) = 2^(2x). ───────────────────────────── (2) Simplify (2⁵)ˣ Recall the power rule: (aᵇ)ˣ = a^(b·x), so:   (2⁵)ˣ = 2^(5x). ───────────────────────────── (3) Simplify (3ˣ)³ Similarly, (3ˣ)³ = 3^(3x). ───────────────────────────── (4) Simplify 2ˣ · 2³ Since the bases are the same, add exponents:   2ˣ · 2³ = 2^(x + 3). ───────────────────────────── (5) Simplify (5³ · 3⁵)ˣ Use the rule (ab)ˣ = aˣ · bˣ:   (5³ · 3⁵)ˣ = (5³)ˣ · (3⁵)ˣ = 5^(3x) · 3^(5x). ───────────────────────────── (6) Simplify 9ˣ · 3^(2x) Since 9 = 3², write:   9ˣ = (3²)ˣ = 3^(2x). Then   9ˣ · 3^(2x) = 3^(2x) · 3^(2x) = 3^(2x+2x) = 3^(4x). ───────────────────────────── (7) Simplify 81ˣ · 27^(2x) Express 81 and 27 as powers of 3:   81 = 3⁴ and 27 = 3³. So,   81ˣ = (3⁴)ˣ = 3^(4x),   27^(2x) = (3³)^(2x) = 3^(6x). Thus,   81ˣ · 27^(2x) = 3^(4x+6x) = 3^(10x). ───────────────────────────── (8) Simplify (5ˣ · 5ˣ) / 25ˣ Write numerator: 5ˣ · 5ˣ = 5^(2x). Write 25 in terms of 5: 25 = 5² so   25ˣ = (5²)ˣ = 5^(2x). Thus,   (5^(2x))/(5^(2x)) = 1. ───────────────────────────── (9) Simplify [(2ˣ)³ · 2ˣ] / 16ˣ Rewrite numerator:   (2ˣ)³ = 2^(3x), so numerator becomes 2^(3x) · 2ˣ = 2^(3x + x) = 2^(4x). Write 16 in terms of 2: 16 = 2⁴ so 16ˣ = (2⁴)ˣ = 2^(4x). Then the expression is 2^(4x) / 2^(4x) = 1. ───────────────────────────── (10) Simplify (7ˣ · 7^(2x)) / ((7² · 7)ˣ) Combine the numerator:   7ˣ · 7^(2x) = 7^(x+2x) = 7^(3x). For the denominator, note:   7² · 7 = 7^(2+1)=7³, so (7² · 7)ˣ = (7³)ˣ = 7^(3x). Thus, the expression becomes 7^(3x)/7^(3x) = 1. ───────────────────────────── (11) Simplify (25 · 9ˣ) / (3ˣ · 3ˣ · 5) Combine the 3ˣ’s in the denominator: 3ˣ · 3ˣ = 3^(2x). Also, note 9 = 3² so 9ˣ = (3²)ˣ = 3^(2x). Then we have:   (25 · 3^(2x)) / (5 · 3^(2x)). Cancel 3^(2x) (provided 3^(2x) ≠ 0) to obtain:   25/5 = 5. ───────────────────────────── (12) Simplify [(2ˣ)³ · 27ˣ] / (8ˣ · (3²)ˣ · 3ˣ) Write (2ˣ)³ = 2^(3x). Also, note 27 = 3³ so 27ˣ = (3³)ˣ = 3^(3x). In the denominator, 8 = 2³ so 8ˣ = (2³)ˣ = 2^(3x); also, (3²)ˣ = 3^(2x) and then extra factor 3ˣ gives 3^(2x+x)=3^(3x). Thus:   Numerator = 2^(3x) · 3^(3x) and denominator = 2^(3x) · 3^(3x), so the fraction is 1. ───────────────────────────── (13) Simplify (12ˣ · 3^(–x)) / (2 · 4ˣ) A good strategy is to express 12 as 3·4. Notice that:   12ˣ = (3·4)ˣ = 3ˣ · 4ˣ. Thus numerator becomes: 3ˣ · 4ˣ · 3^(–x) = (3ˣ · 3^(–x)) · 4ˣ = 3^(0) · 4ˣ = 4ˣ. Denominator is 2 · 4ˣ. Cancel 4ˣ (assuming 4ˣ ≠ 0) giving 1/2. ───────────────────────────── (14) Simplify 32ˣ / 4ˣ Write 32 = 2⁵ and 4 = 2². Then:   32ˣ = (2⁵)ˣ = 2^(5x) and 4ˣ = (2²)ˣ = 2^(2x). Thus,   32ˣ / 4ˣ = 2^(5x)/2^(2x) = 2^(5x – 2x) = 2^(3x). ───────────────────────────── Final Answers (1) 2^(2x) (2) 2^(5x) (3) 3^(3x) (4) 2^(x+3) (5) 5^(3x) · 3^(5x) (6) 3^(4x) (7) 3^(10x) (8) 1 (9) 1 (10) 1 (11) 5 (12) 1 (13) 1/2 (14) 2^(3x) Any answer written in an equivalent form is correct.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

(1) To simplify \( 2^{x} \cdot 2^{x} \), we can use the property of exponents that states \( a^m \cdot a^n = a^{m+n} \). Here, \( 2^{x} \cdot 2^{x} = 2^{x+x} = 2^{2x} \). (2) In \( \left(2^{5}\right)^{x} \), we can apply another exponent rule. This time, \( (a^m)^n = a^{m \cdot n} \). Therefore, \( \left(2^{5}\right)^{x} = 2^{5x} \). Keep those rules in mind, they are very handy for simplifying expressions with exponents!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy